2015
DOI: 10.1097/wco.0000000000000245
|View full text |Cite
|
Sign up to set email alerts
|

What can Duchenne Connect teach us about treating Duchenne muscular dystrophy?

Abstract: Purpose of Review This review aims to describe the benefits and limitations of using the DuchenneConnect patient registry to provide information particularly in regard to active treatment choices in Duchenne muscular dystrophy and their impact on disease progression. Recent findings Clinical trials and natural history studies are difficult for rare diseases like Duchenne muscular dystrophy. Using an online patient self-report survey model, DuchenneConnect provides relevant data that are difficult to gather i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…However, as lack of molecular diagnosis limits access to treatment, genetic counselling and research, a goal of the Registry is to gain sufficient funding so that it can facilitate access to genetic testing for patients who are not able to access testing through the usual pathways. This would be similar to other registries including Duchenne Connect [ 21 ], the Jain Foundation Dysferlin Registry [ 22 ] and the Myotubular Myopathy Registry [ 11 ].…”
Section: Discussionsupporting
confidence: 77%
“…However, as lack of molecular diagnosis limits access to treatment, genetic counselling and research, a goal of the Registry is to gain sufficient funding so that it can facilitate access to genetic testing for patients who are not able to access testing through the usual pathways. This would be similar to other registries including Duchenne Connect [ 21 ], the Jain Foundation Dysferlin Registry [ 22 ] and the Myotubular Myopathy Registry [ 11 ].…”
Section: Discussionsupporting
confidence: 77%
“…Patients and families have contributed to registries (predominantly natural history) through their enrollment and submission of data [ 24 , 30 37 ]. Many of the registries have been established by patient organizations, in collaboration with researchers and healthcare professionals [ 19 , 32 , 34 , 37 – 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recruitment strategy was highlighted as a key variable in this study, where direct physician communication with PMD subjects was found most effective to motivate clinical trial participation. Recruitment for clinical trials in rare diseases can be aided by partnership with patient advocacy organizations and disease consortiums, particularly when a patient registry mechanism exists [ 16 , 37 ]. The NIH RDCRN and United Mitochondrial Disease Foundation (UMDF) have patient-populated registries, respectively designed to recruit patients with all rare and specifically mitochondrial diseases.…”
Section: Discussionmentioning
confidence: 99%